2017
DOI: 10.5812/jjm.44469
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leishmania Species for Cutaneous leishmaniasis in Gonabad, Bardaskan and Kashmar, Central Khorasan, 2015

Abstract: Background: About 90% of cutaneous leishmaniasis (CL) cases are reported from 7 countries including Iran. In this study, the cutaneous leishmaniasis species causing CL in Gonabad, Bardaskan, Kashmar cities in central Khorasan (Iran) were identified by kDNA-PCR. Methods:During the study, 93 suspected patients with CL, who were referred to the dermatology research center in these cities, were evaluated based on age, clinical forms, and place of residence. Direct microscopy was employed for parasitological diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In another study of 164 CL cases from Torghabe-Shandiz, southwest of Mashhad city, all patients were infected by L. tropica (61). Also, 10/12, 20/23, 38/49, and 53/60 CL patients from Bardaskan, Gonabad, Kashmar, and Torbat-e-Heydarieh cities and counties, respectively, which are located in the central and southern regions of this province, were infected with L. tropica (62,63).…”
Section: Northeastern Iranmentioning
confidence: 90%
“…In another study of 164 CL cases from Torghabe-Shandiz, southwest of Mashhad city, all patients were infected by L. tropica (61). Also, 10/12, 20/23, 38/49, and 53/60 CL patients from Bardaskan, Gonabad, Kashmar, and Torbat-e-Heydarieh cities and counties, respectively, which are located in the central and southern regions of this province, were infected with L. tropica (62,63).…”
Section: Northeastern Iranmentioning
confidence: 90%
“…Moreover changes in the climate and in people lifestyles or the lack of immunity in people who immigrate to endemic areas are other risk factors that can increase the incidence of CL in a paerticular area (19,34,35). Similar reasons for the epidemiological changes listed above are likely to underpin the variations in the distribution of Leishmania species observed in Torbat-e Heydarieh, Bardaskan, Kashmar, Khaf, Taybad, Quechan and Chenaran (34,41,42,44). The presence of both L. tropica and L. major species as causes of CL in Sarakhs might be related to its location near an international railroad and in proximity to the border with Turkmenistan; increased movement of people through this region since 2013 is likely to be an additional factor in the observed epidemiological pattern of leishmaniasis (31).…”
Section: Discussionmentioning
confidence: 76%
“…The first step in any control and prevention program for leishmaniasis is the identification of the infectious agents, reservoirs and vectors (35). In recent years, many studies have been conducted in Khorasan-Razavi province with the aim to refine the immunological and molecular diagnosis of the causative Leishmania species (4,6,34,35,(39)(40)(41)(42)46). The aim of this review was to design a new epidemiological picture of CL, using data from several studies performed in Khorasan-Razavi province to identify the boundary shifts for causative agents of CL during a twenty-year period as the basis to new insights for control and prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…According to the present findings, L. major is responsible for leishmaniasis in Esfarayen (based on an unpublished study) and Sabzevar (7), as ZCL was reported in all the 153 patients in the latter city. Mashhad and most of the cities in Khorasan-e Razavi are an endemic region for ACL (7,8). In Iran, ZCL is endemic in the rural regions of the west, the northeast, the center and the southwest, especially in Khuzestan Province.…”
Section: Discussionmentioning
confidence: 99%